World development report 2005 : (Oxford University Press, 2004)
The World Development Report 2005 argues that improving the investment climates of their societies should be a top priority for governments. Drawing on surveys of nearly 30,000 firms in 53 developing countries, country case studies, and other new research, the Report explores questions such as: What are the key features of a good investment climate, and how do they influence growth and poverty? What can governments do to improve their investment climates, and how can they go about tackling such a broad agenda? What has been learned about good practice in each of the main areas of the investment climate? What role might selective interventions and international arrangements play in improving the investment climate? What can the international community do to help developing countries improve the investment climates of their societies?